Cooperative Learning Model in Arabic Language Learning in Class V Madrasah Ibtidaiyah - Mustofa, Arif; Sya’bana, Azka; Yunianto, Teguh; Ahmadnia, Javad (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
The aim of the research is to describe the implementation of the Cooperative Learning model in Arabic language learning in class V of Madrasah Ibtidaiyah. The research method used in this research is qualitative with a case study approach, data collection by observation, interviews and documentation. Data analysis uses the Miles and Huberman model with three stages, namely data reduction, data presentation and drawing conclusions. Data validity uses source triangulation and technical triangulation. The results of the research are that the implementation of the cooperative learning model in Arabic language learning in class V of Madrasah Ibtidaiyah can increase students' active participation and make learning more interesting and enjoyable. Teachers use various methods such as questions and answers, demonstrations, and singing to activate students and provide real learning experiences. There are challenges in learning Arabic, such as differences in ability levels , limited learning time , lack of application of Arabic , student motivation , limited resources and teaching materials , traditional learning approaches , lack of teacher skills in language teaching , difficulties in understanding grammar